The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1186/1472-6785-14-21
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale genetic structure analyses suggest further male than female dispersal in mountain gorillas

Abstract: BackgroundMolecular studies in social mammals rarely compare the inferences gained from genetic analyses with field information, especially in the context of dispersal. In this study, we used genetic data to elucidate sex-specific dispersal dynamics in the Virunga Massif mountain gorilla population (Gorilla beringei beringei), a primate species characterized by routine male and female dispersal from stable mixed-sex social groups. Specifically, we conducted spatial genetic structure analyses for each sex and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 88 publications
(127 reference statements)
4
32
0
Order By: Relevance
“…Father‐daughter inbreeding avoidance was observed within multimale groups, but approximately 10% of infants had parents who were either mother‐son pairs or half‐siblings . The risk of inbreeding can be reduced through sex‐biased differences in dispersal distances, and male mountain gorillas disperse farther than females . Nonetheless, the influences of inbreeding and familiarity among adults on the dispersal patterns of both sexes warrant additional research …”
Section: Fitness Consequences Of Male Dispersalmentioning
confidence: 99%
See 1 more Smart Citation
“…Father‐daughter inbreeding avoidance was observed within multimale groups, but approximately 10% of infants had parents who were either mother‐son pairs or half‐siblings . The risk of inbreeding can be reduced through sex‐biased differences in dispersal distances, and male mountain gorillas disperse farther than females . Nonetheless, the influences of inbreeding and familiarity among adults on the dispersal patterns of both sexes warrant additional research …”
Section: Fitness Consequences Of Male Dispersalmentioning
confidence: 99%
“…In addition to the potential influences of poaching and habituation, humans may have altered the dispersal patterns and social organization of mountain gorillas by reducing the suitable habitat in which to move. Although some emigrating western gorillas and mountain gorillas remain near their natal area, genetic studies have shown long dispersal distances for others . Options to disperse long distances have declined for mountain gorillas in recent decades, as many mountain gorillas now live along a park boundary .…”
Section: Hypotheses For Variation In Social Organizationmentioning
confidence: 99%
“…Survey work around Betampona has shown populations of Indri to be susceptible to habitat fragmentation, with populations possibly becoming locally extinct or being driven out of their historical habitats in as little as 2 yr (Glessner and Britt 2005). Data are lacking on dispersal capabilities of Indri across fragmented landscapes and about dispersal differences between sexes [such as those observed in gorillas by Roy et al (2014)], which may also contribute to these genetic patterns.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ability to retain connectivity between patches, as well as the level of genetic diversity within and between patches, depends on more than absolute distance, as dispersal patterns differ for males and females. Female gorillas always disperse directly between social units and do not travel on their own, but males disperse alone and travel greater distances (Yamagiwa, Kahekwa and Basabose, 2003;Harcourt and Stewart, 2007;Guschanski et al, 2009;Arandjelovic et al, 2014;Roy et al, 2014a). As a result, males may have more of an impact on gene flow within populations and among isolated subpopulations (Bergl et al, 2008;Guschanski et al, 2009;Roy et al, 2014a).…”
Section: Gorillasmentioning
confidence: 99%
“…Female gorillas always disperse directly between social units and do not travel on their own, but males disperse alone and travel greater distances (Yamagiwa, Kahekwa and Basabose, 2003;Harcourt and Stewart, 2007;Guschanski et al, 2009;Arandjelovic et al, 2014;Roy et al, 2014a). As a result, males may have more of an impact on gene flow within populations and among isolated subpopulations (Bergl et al, 2008;Guschanski et al, 2009;Roy et al, 2014a). Human disturbance is believed to have resulted in an abrupt reduction not only in population size, but also in genetic diversity in Cross River gorillas, emphasizing that the impacts of altered landscapes are far more complex than only having fewer apes (Bergl and Vigilant, 2007;Bergl et al, 2008).…”
Section: Gorillasmentioning
confidence: 99%